CODE MIXING USED BY ENGLISH TEACHER IN ENGLISH CLASS AT SMP NEGERI 2 TOMIA - Hanafiah, Wa; Husni, Husni; Hikmah, Nur (English Education Department, 2023)
The problem statement of this research were: 1) What types of code mixing is most used by English teacher in English Class SMP Negeri 2 Tomia; 2) What factors are likely cause to the use of code mixing by English teacher in English class at SMP Negeri 2 Tomia. The objectives of this research to find out; 1) The types of code mixing most used by English teacher in English Class SMP Negeri 2 Tomia; 2) The factors are likely cause to the use of code mixing by English teacher in English class at SMP Negeri 2 Tomia. This research using a sociolinguistic approach with applied descriptive qualitative method. The subject of this research was English teacher at Smp Negeri 2 Tomia. The object of this research is Code Mixing used by English teacher in grade 8A. The instruments used in this research were observation and interview. Based on the finding, the researcher concluded that there were three types of code mixing that used by English teacher, there were Insertions, Alternative and Congruent Lexicalixation. The researcher found the most use type that used by English teacher was Insertion. The results of interview session showed the reason why the teacher used code mixing in English class, first because the teacher was bilingual, this is also due to students' vocabulary skills that are still lacking, and situation because students just get basic English when in junior high school. The students didn’t understand what the teacher’s says when explained the material so the teacher used code mixing and the students could understand and receive it.